Asociación entre el perfil inmunohistoquímico y el desenlace clínico en pacientes con meduloblastoma tratados en un hospital pediátrico peruano, periodo 2013–2022 - Gallegos Mendoza, Milagros (2025)
Medulloblastomas are the most common malignant brain neoplasms in children. Immunohistochemical(IHC) markers can determine a molecular classification, using the markers GAB1, YAP1, β-catenin, P53, and Ki67. The classification of these neoplasms into molecular groups has proven to be clinically and therapeutically significant. The clinical outcomes of medulloblastoma include death, adverse effects or conditions, and tumor recurrence. The objective of this research was to determine the individual association between the IHC markers used for molecular group classification and the clinical outcome in patients with medulloblastoma treated at the Instituto Nacional de Salud del Niño (INSN - National Institute of Child Health) during the period 2013–2022. The population consisted of 58 patients. The individual IHC expression of GAB1, YAP1, β-catenin, p53, and Ki67 in paraffin-embedded biopsies was compared with the clinical outcomes. Descriptive statistics and bivariate analysis were used to determine associations. The desmoplastic/nodular variant was the most commonly observed histological type of medulloblastoma, and there was a high frequency of IHC expression of YAP1 and an association between IHC expression of YAP1 and adverse effects. The clinicopathological characteristics of our cases were similar to those described in China. The finding may be useful as a prognostic marker of adverse effects in pediatric medulloblastoma.